KEPUASAN KELUARGA PENERIMA MANFAAT TERHADAP PELAYANAN PROGRAM KELUARGA HARAPAN DI KELURAHAN ANTAPANI WETAN KOTA BANDUNG - Mubarok, Khayun; Rusmana, Aep; Pribowo, Pribowo (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2025)
Satisfaction is defined as the comparison between expectations and an individual’s perception of the service performance received. In the context of social services, the satisfaction of Beneficiary Families (Keluarga Penerima Manfaat/KPM) with the Family Hope Program (Program Keluarga Harapan/PKH) serves as a key indicator of the program’s effectiveness. This study aims to provide an empirical overview of the level of satisfaction among KPM regarding the quality of PKH services in Antapani Wetan Subdistrict, Bandung City.This research is grounded in the concept of service quality, which includes five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy, along with an additional dimension—beneficiaries' expectations. The study employs a descriptive quantitative approach, with data collected through questionnaires and document analysis. A total of 180 registered PKH beneficiary families were selected as respondents. The measurement scale used was Likert, with face validity for validity testing and Cronbach’s Alpha for reliability testing.The findings show that overall satisfaction among KPM is categorized as very satisfactory, with a total score of 19,934. Each service quality dimension also falls under the "very satisfactory" category: tangibles (3.184), reliability (3.819), responsiveness (3.155), assurance (3.767), empathy (3.673), while the expectation dimension is rated as "satisfactory" with a score of 2.336. Based on the analysis of the issues and needs in the field, the researcher proposes a follow-up program entitled "Technical Guidance for PKH Facilitators on the Technical Guidelines for the Graduation of PKH Beneficiaries" to improve service quality sustainably